What’s up world with Illya Sumanto! / Syed Amir Haikal and Nur Ilianis Adnan - Haikal, Syed Amir; Adnan, Nur Ilianis (Academy of Language Studies, 2022)
In the first episode of "What's Up World!" on 14th October 2021, English Club UiTMCPP invited Illya Sumanto, the founder of Empathy for Youth. Ilya is a youth coach, spoken word artist and she can speak up to 4 different languages fluently (Malay, Indonesian, German, English). This session was hosted by UiTMCPP’s students, Syed Amir Haikal and Syaqille.